Combined administration of catalpol, puerarin, gastrodin, and borneol modulates the Tlr4/Myd88/NF-κB signaling pathway and alleviates microglia inflammation in Alzheimer’s disease - Ren, Huijing; Tang, Ling; Yuan, Zhiying; Liu, Yang; Zhou, Xuejiao; Xiao, Xiao; Wu, Xingyu; Chen, Weihai; Chen, Yi; Wang, Hongjin; Xue, Qiang; Xu, Xiaoyu (Frontiers in Pharmacology, 2024)
Alzheimer's Disease (AD) is a progressive neurodegenerative disorder affecting millions of people worldwide, with no effective treatment currently available. In recent decades, various traditional Chinese medicines (TCMs) and their active ingredients have shown the potential to attenuate the pathogenesis of AD in cellular and animal models. However, the effects of TCM formulas, which are typically administered in practice, have been less studied. This study aims to investigate the therapeutic effects of several formulas consisting of 4 components herbal components: catalpol, puerarin, gastrodin, and borneol, on streptozotocin (STZ)-induced AD models in cells and rats. The new object recognition (NOR), elevated plus maze (EMP), and Morris water maze (MWM) tests were used to evaluate the cognitive functions of rats. Golgi staining, Haematoxylin and Eosin (HE) staining, and Nissl staining analyses were employed assess the physiology of hippocampal tissues. Gene expression profiles were analyzed used transcriptomics and reverse transcription quantitative polymerase chain reaction analysis, while protein expression levels were determined using immunoblotting, immunohistochemical, and immunofluorescence. The production of cytokines was evaluated with enzyme-linked immunosorbent assay. The results demonstrated that the combined administration of these 4 components (CPGB) had superior mitigating effects on AD cell model, as evidenced by the reduced pro-inflammatory cytokine production and decreased deposition of Aβ protein. Further in vivo and in vitro experiments confirmed that varying doses of CPGB formula effectively ameliorated STZ-induced cognitive deficits, as shown by NOR, MWM, and EMP tests, as well as pathological changes in hippocampal tissues and a 3-dimensional brain neurovascular unit (3D-NVU) model, including decreased deposition of Aβ protein and formation of plaques.Transcriptome sequencing and analysis identified 35 genes with significantly altered expression levels due to STZ and CPGB treatment in hippocampal tissues, which were enriched in the Tlr4/Myd88/NF-κB signaling pathway. Interference with this pathway significantly influenced the therapeutic effects of CPGB in the 3D-NVU model.Collectively, these findings suggest that the combined administration of catalpol, puerarin, gastrodin, and borneol offers superior therapeutic effects on AD by modulating the Tlr4/Myd88/NF-κB signaling pathway. This study strengthens the theoretical foundation for using TCMs to treat AD, proving new insights and references for alleviating and treating AD.